Special forces guerrilla warfare manual - Wimberley, Scott (Paladin Press, 1997)
This handy manual is a primer in the many facets of a successful guerrilla campaign as taught by the pros in Special Forces. Covering everything from the first acts of sporadic rebellion to the final overthrow of a tyrannical government and establishment of a just, democratic society, it is a fascinating tutorial in modern armed resistance.